2019
DOI: 10.1186/s13287-019-1192-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the characteristics and expression profiles of coding and noncoding RNAs of human dental pulp stem cells in hypoxic conditions

Abstract: BackgroundHuman dental pulp stem cell (DPSC)-mediated regenerative endodontics is a promising therapy for damaged teeth; however, the hypoxic environment in root canals can affect tissue regeneration. In this study, we investigate the characteristics and possible regulatory mechanisms of DPSC function under hypoxic conditions.MethodsHuman DPSCs were cultured under normoxia (20% O2) and hypoxia (3% O2). DPSC proliferation and osteo/odontogenic differentiation potential were assessed by Cell Counting Kit-8 (CCK8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 68 publications
2
27
0
Order By: Relevance
“…We have shown that the cell isolation and expansion at low [O 2 ] led to an increased proliferation capability of SCAPs and to a preserved expression of the classical MSC markers with a slight decrease of CD105, as already reported [43]. A recent report with DPSC isolated at 21% O 2 and expanded at either 21% or 3% O 2 (as in our EXP II) also demonstrated an advantage of cell growth under low [O 2 ] compared with ambient air [15]. Among the different markers analyzed, CD49f and SSEA4 remained highly expressed under low [O 2 ] in comparison with ambient air.…”
Section: High Proliferative Capacity But Not Better Clonogenicity Undsupporting
confidence: 87%
See 3 more Smart Citations
“…We have shown that the cell isolation and expansion at low [O 2 ] led to an increased proliferation capability of SCAPs and to a preserved expression of the classical MSC markers with a slight decrease of CD105, as already reported [43]. A recent report with DPSC isolated at 21% O 2 and expanded at either 21% or 3% O 2 (as in our EXP II) also demonstrated an advantage of cell growth under low [O 2 ] compared with ambient air [15]. Among the different markers analyzed, CD49f and SSEA4 remained highly expressed under low [O 2 ] in comparison with ambient air.…”
Section: High Proliferative Capacity But Not Better Clonogenicity Undsupporting
confidence: 87%
“…Further studies are required to better understand if there is a link between high CD49f and SSEA4 expression and proliferation in SCAPs. [15,62]. The media used for these experiments have been optimized under 21% O 2 and might lack important components essential for efficient differentiation at late passage.…”
Section: High Proliferative Capacity But Not Better Clonogenicity Undmentioning
confidence: 99%
See 2 more Smart Citations
“…Expanding this study to include more DPSC isolates with variable expression of these pluripotency biomarkers will provide substantial information that could validate the findings of the current study. In addition, a more comprehensive evaluation of other potential biomarkers, such as non-coding microRNA, may provide more specific and targeted methods for bioengineering and biotechnology applications utilizing DPSC [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%